The Networks of New Haven Culture, 1800-1850. - Ellis, Scott (2011)
Sabbatical research investigating the literary culture of New Haven, Connecticut, during the first half of the 19th century, encompasing book importers, booksellers, publishers, newspapers, periodicals, libraries, and literary societies. Based on extensive local collections dispersed throughout local repositories.
Keywords: dept.eng; faculty_collection; sabbatical_report